(untitled) (City Dental College Journal, 2012)
Purpose: The objective of this study was to evaluate the correlation between maxillary canines and the facial landmarks including interalar width (IAW) and intercommissural width (ICoW) in a group of Bangladeshi people. Materials and methods: One hundred Bangladeshi subjects aged 18 35 years were selected. Irreversible hydrocolloid impression of the upper arch was taken and a cast was poured with dental stone.The interalar width (IAW) and intercommissural width (ICoW) were measured using digital vernier caliper. Intercanine tip (ICTW) and width of the distal surface of the canine (WDC) were measured from the cast using digital caliper. Results: The correlation between ICTW-IAW was 0.246. There was no correlation between ICTW-ICoW. The correlation between WDCIAW and WDC-ICoW were 0.342 and 0.235 respectively (p< .05). Conclusion: Both interalar width and intercommissural width had a weak correlation with the position of maxillary canine in this Bangladeshi subject group. For the construction of a pleasing and harmonious complete denture esthetic and phonetic outcomes are recommended to be considered in combination with facial landmarks. DOI: http://dx.doi.org/10.3329/cdcj.v9i2.12315 City Dental College J. Volume-9, Number-2, July-2012